Where Analytics Gets It Wrong - Nicholas Watanabe; Johan Rewilak (Journal of Applied Sports Management, 2022)
The authors will discuss the emergence of analytics, and outline with examples, certain problems that plague both academics and practitioners in their approach to using sport analytics.
Keywords: sport analytics; sport management; analytics